PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS X MIPA SMA NEGERI 12 MAKASSAR - Nurfadia; Kasma F Amin; Umar Mansyur (STKIP Subang, 2023)
Application of the Numbered Head Together Type Cooperative Learning Model to Increase Student Learning Activeness in Indonesian Language Learning Class X MIPA SMA Negeri 12 Makassar The research aims to determine the process and results of applying active speaking students in class X MIPA SMA Negeri 12 Makassar and to find out the results of increasing students' speaking activeness class X MIPA 4 SMA Negeri 12 Makassar uses the Numbered Head Together cooperative learning model. This research is a classroom action research, there are two cycles in its implementation. Each cycle has four stages, namely planning, implementing, observing and reflecting. The subjects of this study were 25 students of class X MIPA 4 SMA Negeri 12 Makassar. Data collection is done by test. In the planning stages of cycle I and cycle II, the learning implementation is the same, the difference is in the learning steps. If the learning steps carried out in cycle I are not optimal or have an effect on the achievement of learning outcomes, then cycle II student achievement is better or said to be complete with the learning outcomes achieved after the application of the cooperative learning model shows the results that in cycle I completeness is 70% and in cycle II completely classical by 89% of students who are active in speaking. The conclusion from the results of this study is that the Numbered Head Together learning model can increase student learning activity in Indonesian language class X MIPA 4 SMA Negeri 12 Makassar.